PERAN STRES AKADEMIK TERHADAP KOMPETENSI KEGAWATDARURATAN PADA MAHASISWA VOKASIONAL KEPERAWATAN - Yektiningsih, Erwin; Rahmawati, Erni; Kosasih, M Ikhwan; Maryati, Heni; Anggar, Roshinta Sony; Wilujeng, Atik Pramesti (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Academic stress is prevalent among nursing students and may hinder the acquisition of emergency nursing competencies, which require high discipline and mental readiness. Objective: This study aimed to examine the relationship between academic stress and emergency nursing competency among diploma (D-III) nursing students in East Java. Method: A cross-sectional design was employed with 472 nursing students selected through purposive sampling. Academic stress was measured using the Student Stress Questionnaire (CSSQ), while competency was assessed based on the AIPVIKI emergency nursing curriculum. Data were analyzed using Spearman’s rho. Results: Most respondents experienced mild academic stress (69.5%) and demonstrated moderate competency levels (67.8%). A significant negative correlation was found between academic stress and competency (r = -0.234; p < 0.001). Conclusion: Higher academic stress is associated with lower emergency nursing competency. Educational institutions should implement effective stress management strategies and foster supportive learning environments to optimize competency development.